International Migration, Kinship Networks and Social Capital in Southwestern Nigeria - Akanle, Olayinka; Fayehun, Olufunke A.; Adejare, Gbenga S.; Orobome, Otomi A. (Journal of borderlands studies, 2021)
International migration attracts global concern as international migration and its remittances are highly important mechanisms with profound implications for family, community, and national and international sustainability across borderlines. The demand for workers in most industrialized countries in order to sustain national economies and aspiration of migrants from less industrialized nations for better job opportunities and better ways of life have continued to foster migration and challenge constructions of social capital. As well as various push and pull factors, kinship networks and familial social relations serve as major drivers of migration. Consequently, various social structures and development projectiles in the giving and receiving nations are implicated. Thus, this study delved into interrogating the contours of how remittances in terms of patterns and perceptions embedded in migrations and social relations of migrants and their kin in selected locations in Ibadan. This study utilized a purely qualitative method of research because the subject matter focuses on making sense of meanings people attach to migration, remittance and supports as social capital towards understanding migration dynamics. Data were purposively collected through in-depth interviews in Ibadan metropolis, Nigeria. A total of 40 interviews were conducted. This article makes an important contribution to the data and literature on motivations to migrate.